These precious days [compact disc, unabridged] : essays - Patchett, Ann (Harper Audio, 2021)
A literary alchemist, Patchett plumbs the depths of her experiences to create gold: engaging and moving pieces that are both self-portrait and landscape, each vibrant with emotion and rich in insight. Turning her writer's eye on her own experiences, she transforms the private into the universal, providing listeners a way to look at their own worlds anew, and reminds how fleeting and enigmatic life can be.